In vitro studies of Searsia lancea leaf extracts against multi-drug resistant bacterial isolates from clinical cases of bovine mastitis - McGaw, Lyndy Joy (University of Pretoria, 2024)
Thesis (PhD (Paraclinical Sciences))--University of Pretoria, 2023.